Isolation and molecular characterization of Vibrio fluvialis from diarrheal children in Nasiriyha City - H.Mezal, Ezat; A .mohammed , Hawraa; kaream hanan, Zaman (University of Thi-Qar Journal of Science, 2019)
The objective of this study was to investigate the incidence, molecular features, as well as the antimicrobial susceptibilities of Vibrio.fluvialis isolated from diarrheal (children) in Nasiriya city from (July 2016 to February2017) . A total of (20) samples of Vibrio. fluvialis were collected and analyzed by bacteriological, molecular and antimicrobial methods. Green and yellow bacterial colonies were recovered on thiosulfate citrate bile salt sucrose agar plates. The phenotypic characteristics of the isolates, including morphological, physiological and biochemical traits were determined and confirmed using API 20E system. Following isolation, the 16S rRNA gene specific for the genus Vibrio.fluvailis was investigated by using PCR. Antimicrobial susceptibility to 10 antimicrobial agents was determined by the disc agar-diffusion method .In this study the isolates were more resistance to polymaxin B (70%) & streptomycin (65%) and tetracycline (60%),while doxycycline was (60%) ,ampicillin and chloramphenicol (55%) ,while trimethoprim was resistance (50%).while was more sensitative to Nalidixic acid &Azithromycin (35%)and ciprofloxacin (45%). The study showed an increase presences of Vibrio.fluvialis in diarrheal children &ahight resistance of many antimicrobial agent that importance to find suitable methods to control the infection transmission.